Ammonia volatilization from urea as affected by tropical‐based palm oil mill effluent (Pome) and peat - Siva, K. B.; Aminuddin, H.; Husni, M. H. A.; Manas, A. R. (Taylor and Francis Group, 1999)
Ammonia (NH3) volatilization is a major pathway of nitrogen (N) loss which limits the efficiency of urea as a fertilizer when surface-applied to soils. High pH and low cation exchange capacity in soils have been identified as the principal causes of NH3 volatilization from urea. The several approaches proposed to correct such inefficiency in urea were, thus far, fundamentally based upon delay of urea dissolution and impedance of urea hydrolysis. An attempt was made to establish a preferred environment within the urea-soil reaction zone (microsite) using palm oil mill effluent (POME) and peat. The organic materials were separately matrixed with urea into pelletized form and evaluated under laboratory regimes for the per cent NH3 volatilization, pH change, and ammonium-nitrogen (NH4-N) recovery. Estimation of NH3 volatilization was carried out using a closed-dynamic air- flow system. Determination of the chemical and physical attributes of soils and materials, and the measurement of the parameters studied were done using standard procedures. Results showed that reduction in NH3 volatilization by peattreated urea was more pronounced than that of POME in both soils. Such reduction was accompanied by a corresponding increase in NH4 recovery and a decrease in pH particularly at the microsite. The use of differing matrix ratios did not yield significant variation in the performance of the matrixing agents. Acidification of POME and peat resulted in impedance of urea movement from microsite to outersite. Generally, results indicated that the ability of peat and POME to reduce NH3 volatilisation from urea was due to NH4 adsorption.